Rock magnetic and palaeomagnetic study of the archaean granites from Hyderabad, India - Goutham, M.R.; Sandhya, R.; Rao, B. Madhusudhan; Patil, S.K.; Murthy, B.V.S. (My University, 2010)
Samples from Hyderabad granitic region are studied for their rock magnetic and palaeomagnetic behaviour. There are considerable differences between the pink and gery granites in the rock magnetic properties such as Intensity of natural remanent magnetization (Jn), magnetic susceptibility () and Koenigsberger’s ratios (Qn) and indicates that these granites are of two different origins. Average values of NRM intensity,  and Qn are found to be 488 and 637 Am- 1; 1689 and 1780; and 9 and 19.7 for pink and gray granites respectively. Two different mean palaeomagnetic directions were obtained for these rocks after af demagnetization which are D/I = 159o/-25o and 268o/-40o. The corresponding palaeomagnetic poles lie at 69S/160E and 8S/327E respectively. Based on the statistics former direction 159o/-25o is considered as the palaeomagnetic direction of Hyderabad granitic region.
Keywords: Rock magnetic; Palaeomagnetic study; Archaean granites; Hyderabad